PERFORMANCE ATTRIBUTES OF DECK AND ENGINE CADETS ONBOARD DUTCH MERCHANT SHIPS - Ochavillo, Gregorio S. (PEOPLE: International Journal of Social Sciences, 2016)
This study was conducted to determine the attributes that influenced the performances of the deck and engine cadets of the Palompon Institute of Technology (PIT) during their apprenticeship training onboard Dutch ships. The study was a descriptive-survey method utilizing a standardized survey instrument provided in the Quality Management System of the Institute’s College of Maritime Education. The subjects considered were deck and engine cadets who were onboard Dutch ships for their 1 year apprenticeship training. While deck and engine management level officers were the respondents. Results revealed the performances of the cadets were highly influenced by the associated attributes as regards “Personal Qualities” and “Professional Knowledge and Skills.” Moreover, as regards to “Outlook/Expectations”, majority of deck and engine cadets were expected able to perform their tasks independently as ship’s officers upon completion of the onboard training period of one year; while there were few from both groups that were expected able to perform his/her task independently as ship’s officer only after an additional on board training period. Furthermore, it was found out the academic performance of the deck cadets was satisfactory with high grades while the engine cadets with less satisfactory. Finally, the relationship between the performance attributes and academic performance in both groups of respondents were established.